2002
DOI: 10.1046/j.1442-200x.2002.01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Helicobacter pylori infection is not accurate for children aged below 10

Abstract: These facts suggested that an immature immune response or tolerance to H. pylori exists in childhood and serodiagnosis of H. pylori infection is less useful in children aged below 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 7 publications
(14 reference statements)
2
35
0
Order By: Relevance
“…Sensitivity was found to be lower than that of the mothers and this could be attributed to the immature immune response or tolerance to H. pylori that exists in childhood and thus serodiagnosis of H. pylori infection is less useful in children. Similar findings were reported by Okuda et al (2002) who compared H. pylori IgG and IgA Abs with H. pylori stool Ags (Okuda et al, 2002). Our results were in concordance with that of Pourakbari et al (2013) who found that ELISA-IgG serum tests in children showed high specificity, but low sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Sensitivity was found to be lower than that of the mothers and this could be attributed to the immature immune response or tolerance to H. pylori that exists in childhood and thus serodiagnosis of H. pylori infection is less useful in children. Similar findings were reported by Okuda et al (2002) who compared H. pylori IgG and IgA Abs with H. pylori stool Ags (Okuda et al, 2002). Our results were in concordance with that of Pourakbari et al (2013) who found that ELISA-IgG serum tests in children showed high specificity, but low sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…We reported similar results that serodiagnosis by HM-CAP EIA on Japanese asymptomatic children under 10 years of age had 51.4% sensitivity and 97.2% specificity in reference to H. pylori stool antigen test (HpSA test) (20). In contrast, a commercially available urine-based EIA test, URINELISA, is highly reliable with 92.8% sensitivity and 95.8% specificity in reference to the 13 C-labeled urea breath test (UBT) and HpSA test on the same age group of a similar population (21).…”
supporting
confidence: 57%
“…The serologic test for H. pylori infection can be easily performed in epidemiologic studies using stored sera. However, concerns regarding validity have been raised due to its lower sensitivity and specificity as compared with the HpSA tests and urea breath tests [30]. On the other hand, other recent studies have reported high accuracy of the serum antibody test in children.…”
Section: Discussionmentioning
confidence: 99%
“…One factor affecting the results may have been the age of participants in the current study. Previous reports have stated that serum antibody tests are not useful in children younger than 10 years because their immune response is immature [24, 30]. In one study, which examined serum H. pylori antibodies using the ELISA method in 157 children (mean age 5.6 ± 4.6 years), the test was found to have a sensitivity of 54.5% in children under the age of 10 years and a sensitivity of 100% in those aged 10 years and above [19].…”
Section: Discussionmentioning
confidence: 99%